Extending the Lifespan of Garments Globally through Local Upcycling: A Mixed-Methods Approach - Vanacker, Hester Lies; Lemieux, Andrée-Anne; Laitala, Kirsi Maria; Dindi, Michelle; Lamouri, Samir; Bonnier, Sophie (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Extending the lifespan of garments is considered a solution to counteract a culture that views them as disposable objects. However, how this is to be done in practice remains unclear. Using a multimethod approach, this study aims to investigate how garments can adapt to their local environment(s) and user(s) so that they can go through different life cycles. To this end, the authors combined data from semi-structured interviews conducted in five different countries and enriched them through triangulation with available literature. We discovered that the durability of garments is dynamic in nature, and that upcycling is a method to extend their lifespans. Furthermore, how the materials of the garment are perceived locally, influences if it is considered eligible for upcycling. As local conditions have not been considered in the definition of the concept so far, we have defined local upcycling as: a process in which materials and garments that are considered worth discarding in their current state are transformed into a product of higher value that is suitable for the local environment, eliminating the need for a new product. Although the lack of field research at the organizational level is a limitation of this study, the authors view this as a potential avenue for future research.